Value Creation of a Tech Startup in Modern Approaches to Strategic Management - Mateusz TRZASKA; Rafal TRZASKA (Communications of International Proceedings, 2022)
The purpose of this research is to investigate how tech startups generate value through their development stages. Tech startups are organizations looking for a scalable, repeatable and profitable business model underpinned in new technology products/ services or applying existing technology into product/services in a new way. The research is based on critical literature review, desk research, deductive thinking and authors’ observations on the most prominent tech players. The study showed that tech startup generates value by combining two strategic management paradigms: innovative and entrepreneurial approach to strategy, and network approach to strategy. Value is generated from different rents depending the adopted approach to strategy. The originality of the research is in identified value generation methods depends on the startup development stage and the combination of two paradigms.
Keywords: strategic management; inter-organizational network; tech startups